2017
DOI: 10.13189/eer.2017.050510
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Water Disinfection by Solar Radiation

Abstract: A primary concern of developing countries throughout the world is that of obtaining safe drinking water. Waterborne diseases are still common in developing countries since drinking water sources are contaminated and the conventional rural water treatment plants are often inefficient to produce safe drinking water. This situation in developing countries is a major problem in terms of preventing public health. It is estimated that diarrhea accounted for 99% of the 69 million deaths among children before the age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Luzi et al [75] stated that on a clear sunny day, 6 h of exposure is enough compared with cloudy conditions. The effectiveness of SODIS was found to be the best in locations with significant amounts of strong sunlight during midday, mostly located around the equator [76]. Various studies have been conducted to overcome the weather issue in term of partially sunny or during cold season and enhance SODIS; Sommer et al [77] suggested using darker containers or painting the underside of them with black to enhance the thermal disinfection.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Luzi et al [75] stated that on a clear sunny day, 6 h of exposure is enough compared with cloudy conditions. The effectiveness of SODIS was found to be the best in locations with significant amounts of strong sunlight during midday, mostly located around the equator [76]. Various studies have been conducted to overcome the weather issue in term of partially sunny or during cold season and enhance SODIS; Sommer et al [77] suggested using darker containers or painting the underside of them with black to enhance the thermal disinfection.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The conventional method is based on UV light. However, solar light is also efficient for the deactivation of biohazards [68,69] and research regarding its application is increasing using several combinations (Figure 1). when monopersulfate was used as additive.…”
Section: Light Application For Disinfectionmentioning
confidence: 99%
“…Based on this finding, the idea of solar water disinfection, or SODIS, one important point-of-use technology for drinking water treatment, has been developed [100,101]. In many regions of the world, the UVA part of sunlight is employed for disinfection purposes [33,69,100,101]. The germicidal effect of sunlight is attributed to the synergistic effect of solar UV light and mild-thermal heating that is produced during exposure [69,102,103].…”
Section: Solar Disinfectionmentioning
confidence: 99%
See 2 more Smart Citations